2019
DOI: 10.1103/physrevresearch.1.013012
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry indicators for topological superconductors

Abstract: The systematic diagnosis of band topology enabled by the method of "symmetry indicators" underlies the recent advances in the search for new materials realizing topological crystalline insulators. Such an efficient method has been missing for superconductors because the quasi-particle spectrum in the superconducting phase is not usually available. In this work, we establish symmetry indicators for weak-coupling superconductors that detect nontrivial topology based on the representations of the metallic band st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 55 publications
(88 reference statements)
4
70
0
Order By: Relevance
“…Furthermore, we show that there exists a consistent definition of an "atomic-limit superconductor" as an "array" of zero-dimensional superconductors [39]. Our definition is consistent with the definition in the published version of Skurativska et al [65]. In the weak-pairing limit, the symmetrybased indicators derived here can be expressed in terms of the normal part of the Hamiltonian only, so that in that limit our approach offers the same computational advantages as the approaches that rely on the weak-pairing limit at the outset.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Furthermore, we show that there exists a consistent definition of an "atomic-limit superconductor" as an "array" of zero-dimensional superconductors [39]. Our definition is consistent with the definition in the published version of Skurativska et al [65]. In the weak-pairing limit, the symmetrybased indicators derived here can be expressed in terms of the normal part of the Hamiltonian only, so that in that limit our approach offers the same computational advantages as the approaches that rely on the weak-pairing limit at the outset.…”
Section: Introductionsupporting
confidence: 84%
“…In the weak-pairing limit, superconducting order parameter much smaller than energy scales typical for the normalstate band structure, the band labels N k s α and p k s α of the BdG Hamiltonian H (k s ) at the high-symmetry momentum k s can be expressed in terms of zero-dimensional topological invariants of the normal-state Hamiltonians h(k s ) and h(−k s ). For N k s α one has [65,67,68]…”
Section: E Weak-pairing Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 34,35,64 ] Symmetry‐based indicators were initially constructed for insulators, and have been recently extended to superconductors. [ 57,65–70 ] Although symmetry‐based indicators in general do not provide a full classification, their construction and subsequent application resulted in the discovery of many new topological insulator materials [ 71,72 ] . It remains to be seen if the same will be the case for topological superconductors.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported results useful for determining the topological invariants of 3D TCSCs from the symmetry indicators in the normal state. [44][45][46][47][48] In the present paper, we extend these studies by systematically elucidating the magnetic response of Majorana Kramers pairs with one-dimensional invariants ν[U] ∈ Z 2 protected by an order-2 symmorphic or nonsymmorphic symmetry U. In the symmorphic case, an energy gap occurs in the Majorana Kramers pair when an applied magnetic field breaks the symmetry U.…”
mentioning
confidence: 99%